Borders, paths and orientations: assembling the higher education research field as doctoral students and supervisors. Issue 3 (3rd April 2021) - Peseta, Tai; Kligyte, Giedre; Bell, Amani; Hardiman, Brittany; Leadbeatter, Delyse; Pizzica, Jenny; Saliba, Gina; Salisbury, Fiona; Thomson, Kate; Yucel, Robyn
ABSTRACT: While higher education (HE) is entrenched as a context for scholarly inquiry in Australian universities, there remains contest about it as a research field. Unlike other forms of 'Education', in Australia there is no undergraduate programme inducting students into HE's key questions, scholars, and inquiry modes. For new doctoral students, learning to make an original contribution to a field described as a practice, a discipline, and context is a persistent challenge. In this paper, we 'think with' the concepts of borders, paths and orientations to interrogate our practices as doctoral students and supervisors in the field of HE research, under the formation #thesisthinkers. We offer multiple accounts of how #thesisthinkers invites us to confront HE as a field, and in particular, how #thesisthinkers has invigorated us to build a useable landscape of the HE research field that sustains multiple pathways for doctoral researchers, leaving behind traces for others to tread.